Effect of ultrasonography surveillance in patients with liver cancer: a population-based longitudinal study. Issue 6 (23rd June 2017) - Chiang, Jui-Kun; Chih-Wen, Lin; Kao, Yee-Hsin
Abstract : Objective: Liver cancer is a growing global public health problem. Ultrasonography is an imaging tool widely used for the early diagnosis of liver cancer. However, the effect of ultrasonography surveillance (US) on the survival of patients with liver cancer is unknown. Therefore, this study examined the association between survival and US frequency during the 2 years preceding patients' liver cancer diagnosis. Methods: This population-based longitudinal study was conducted in Taiwan, a region with high liver cancer incidence, by using the National Health Insurance Research Database. We compared survival between patients who received US three times or more (≥3 group) and less than three times (<3 group) during the 2 years preceding their liver cancer diagnosis, and identified the predictors for the ≥3 group. Results: This study enrolled 4621 patients with liver cancer who had died between 1997 and 2010. The median survival rate was higher in the ≥3 group (1.42 years) than in the <3 group (0.51 years). Five-year survival probability was also significantly higher in the ≥3 group (14.4%) than in the <3 group (7.7%). The multivariate logistic regression results showed that the three most common positive predictors for receiving three or more US sessions were indications of viral hepatitis, gallbladder diseases and kidney–urinary–bladder diseases; the most common negative predictors for receiving three or more US sessions were male sex and indications of abdominal pain. Conclusion: Patients with liver cancer who received US three times or more during the 2 years preceding their liver cancer diagnosis exhibited a higher 5-year survival probability.